2016
DOI: 10.1007/s11814-015-0292-7
|View full text |Cite
|
Sign up to set email alerts
|

Phenol decomposition in water cathode of DC atmospheric pressure discharge in air

Abstract: We studied phenol decomposition in aqueous solution under the action of DC discharge at atmospheric pressure in air. The decomposition efficiency was 0.017 molecules per 100 eV. When the kinetics of forming destruction products was studied in detail, the peculiarities of air plasma action were revealed for the first time. Plasma action not only results in the formation of oxygen-containing products, which are usually formed under oxygen plasma action (hydroxyhenols, carboxylic acids, aldehydes), but also the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 43 publications
3
3
0
2
Order By: Relevance
“…Really, the formation of nitrite and nitrate ions was observed in the study [32] for the same discharge as presented here. The acidity change (Fig.…”
Section: Kinetic Model Kinetic Model For Aqueous Solutionssupporting
confidence: 64%
“…Really, the formation of nitrite and nitrate ions was observed in the study [32] for the same discharge as presented here. The acidity change (Fig.…”
Section: Kinetic Model Kinetic Model For Aqueous Solutionssupporting
confidence: 64%
“…These properties were previously evidenced by microbiologists [60,61]. Rybkin et al [62] recently reported on the nitration of phenol by DBD discharge. The occurrence of such reactions in organic pollutant abatement, as well as in bacterial inactivation, suggests the formation of ions (e.g.…”
Section: Peroxynitrite and Peroxynitrous Acidsupporting
confidence: 52%
“…Therefore, the relationship between the rates of reactions (1) and (2-4) can determine the behaviour of peroxide concentration [12]. Such a course of events seems to describe the simplest situation, but it does not always fit the experimental observations.…”
Section: Peroxide Formationmentioning
confidence: 99%
“…Plasma treatment realised in various forms of plasma discharge is a very effective attractive alternative to the methods of solution treatment mentioned above. Plasma discharge was successfully used to treat wastewaters contaminated with herbicides/pesticides, decompose pharmaceuticals, surfactants, sulfonol, phenol and textile dyes [9][10][11][12]. Many of the researches have focused on the decomposition of organic compounds which are key contaminants in source water.…”
Section: Introductionmentioning
confidence: 99%